Design and Development of Micro-Power Generating Device for Biomedical Applications of Lab-on-a-Disc - Joseph, Karunan; Ibrahim, Fatimah; Cho, Jongman; Thio, Tzer Hwai Gilbert; Al-Faqheri, Wisam; Madou, Marc (Joseph et al, 2015)
The development of micro-power generators for centrifugal microfluidic discs enhances the platform as a green point-of-care diagnostic system and eliminates the need for attaching external peripherals to the disc. In this work, we present micro-power generators that harvest energy from the disc’s rotational movement to power biomedical applications on the disc. To implement these ideas, we developed two types of micro-power generators using piezoelectric films and an electromagnetic induction system. The piezoelectric-based generator takes advantage of the film’s vibration during the disc’s rotational motion, whereas the electromagnetic induction-based generator operates on the principle of current generation in stacks of coil exposed to varying magnetic flux. We have successfully demonstrated that at the spinning speed of 800 revolutions per minute (RPM) the piezoelectric film-based generator is able to produce up to 24 microwatts using 6 sets of films and the magnetic induction-based generator is capable of producing up to 125 milliwatts using 6 stacks of coil. As a proof of concept, a custom made localized heating system was constructed to test the capability of the magnetic induction-based generator. The heating system was able to achieve a temperature of 58.62°C at 2200 RPM. This development of lab-on-a-disc micro power generators preserves the portability standards and enhances the future biomedical applications of centrifugal microfluidic platforms.